Synthesis, IR Spectrum, Thermal Analysis, and Crystal Structure of the Cyano-Bridged Heteronuclear Polymeric Complex: [Zn(teta)Ni(μ-CN)2(CN)2]n - Kürkçüoǧlu, G.S.; Yeşilel, O.Z.; Kavlak, I.; Büyuk̈güngör, O. (Wiley-VCH Verlag GmbH, 2009)
The heteronuclear polymeric complex, [Zn(teta)Ni(μ-CN) 2(CN)2]n (teta: triethylenetetramine), was synthesized and characterized by elementel analysis, FT-IR spectroscopy, thermal analysis and single crystal X-ray diffraction techniques. The complex crystallizes in the monoclinic system, space group P21/c and in which the ZnII ion exhibits a distorted octahedral coordination by one tetradentate teta ligand and two bridging cyano groups as a trans position, whereas the NiII ion has square planer coordination and is coordinated by four cyano ligands. The decomposition reaction takes places in the temperature range 30-600°C in the static air atmosphere. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.
Keywords: Cyano-Bridged Complex; Tetracyanonickelate Complex; Triethylenetetramine Complex